The unknown eye: Physiology, phenomenology and photography - Gray, Michael (Queensland Centre for Photography, 2014)
The purpose of this paper is to explore specific concepts behind the media employed in my artistic series, ‘New Australian Plants and Animals’, which combines photographs, sculptures and installations based on single element lenses. There are two main discussions within the paper that approach the subject in terms of how the eye’s physiology affects the way we visually experience phenomena and how that, in-turn, can be applied to works of art. One is to discuss the difference between the visual characteristics of images unconsciously experienced inside the eye as opposed to the quality of conscious visual perception. The other discussion is based on how these qualities and characteristics relate to either single element lenses or traditional compound photographic lenses. The starting point for this research is to acknowledge that the eye does not see by itself. The information gathered inside the eye is a preconscious phenomenon as opposed to the conscious interpretation of that phenomenon that we call perception. Given the optical and sensory ability of the eye cannot produce an overall sharp image, it is the mind that is mostly responsible for perception. The only visual ‘truth’ we can discuss is what the mind produces and as this is somewhat of a virtual process it highlights potential ontological issues.The artworks within ‘New Australian Plants and Animals’ aim to replicate what I call, the ocular aesthetic, the hypothetical visual characteristics of images projected onto the retina. I align the artistic process of isolating the ocular part of vision with the phenomenological concept of bracketing as I attempt to remove the mind’s role in perception and re-introduce the viewer to a primordial, primordial visual experience. As the basis for my PhD, ‘New Australian Plants and Animals’ conceptualises the possible ways Terra Australis exerts itself over the colonial psyche. In my exegesis I discuss parallels between the ocular part of vision and this process. Both are hidden from our consciousness and both are immeasurable yet significant in terms of influencing how the physical self interacts with the physical world.